Left atrial volume stress echocardiography in chronic coronary syndromes. (25th November 2020) - Morrone, D; Arbucci, R; Wierzbowska-Drabik, K; Ciampi, Q; Peteiro, J; Agoston, G; Varga, A; Camorazano, A.C; Boshchenko, A; Dekleva, M; Simova, I; Citro, R; et al.
Abstract: Background: An enlarged left atrial volume index (LAVI) at rest mirrors increased LA pressure and/or impairment of LA function. A cardiovascular stress may acutely modify LAVI within minutes. Purpose: To assess the feasibility and functional correlates of LAVI-stress echocardiography (SE) Methods: Out of 514 subjects referred to 10 quality-controlled labs, LAVI-SE was completed in 490 (359 male, age 67±12 yrs, ejection fraction 60±10%) with suspected or known chronic coronary syndromes (n=462) or asymptomatic controls (n=28). The utilized stress was exercise in 177, vasodilator in 167, dobutamine in 146. LAVI was measured with the biplane disk summation method. SE was performed with the ABCDE protocol. In a single center sub-study in 50 subjects, including 28 controls and 22 patients, also peak longitudinal atrial strain (PALS, %) was measured as an index of LA reservoir function. Results: The intra-observer and inter-observer LAVI variability were 5% and 8%, respectively. Δ-LAVI changes (stress-rest) were negatively correlated with resting LAVI (r=−0.271, p<0.001), heart rate reserve (r=−0.239, p<0.001), and Δ-PALS (n=50, r=−0.374, p=0.007).LAVI-dilators were defined as those with stress-rest increase ≥6.8 ml/m 2, a cutoff derived from a calculated reference change value above the biological, analytical and observer variability of LAVI. LAVI dilation (see figure) occurred in 56 patients (11%). At multivariable logistic regression analysis, B-lines ≥2 (OR: 2.586, 95% CI =1.1293–5.169, p=0.007) and abnormal left ventricular contractile reserve (OR: 2.207, 95% CI=1.111–4.386, p=0.024) were associated with LAVI dilation. Conclusion: LAVI-SE is feasible, with high success rate and low variability, in patients with chronic coronary syndromes. A wet (increased B-lines) and weak (reduced LV contractile reserve and LA reservoir function) heart frequently portends LAVI dilation during stress. Funding Acknowledgement: Type of funding source: None